Mondor syndrome associated with breast augmentation: case report - Maria Clara Gomes de Morais; Karley Silva Almeida; Gabriel Carvalho Fiusa; Rafael Rodolfo Tomaz de Lima; Karla Patrícia Cardoso Amorim (Revista Brasileira de Cirurgia Plástica)
The breast form of Mondor syndrome is a rare and self-limited condition characterized by thrombophlebitis of the superficial veins of the breast. Understanding this syndrome is extremely important for correct diagnosis and precise, non-iatrogenic treatment, given that it has a considerable relationship with breast carcinoma. This case report portrays the emergence of Mondor syndrome in a young 22-year-old patient, after breast augmentation. The characteristic sign of the condition, the fibrous cord, appeared in the right breast from the twenty-third day after surgery, disappearing completely after 10 weeks. The diagnosis was given by the plastic surgeon who followed the patient through anamnesis and physical examination, without the urgency of a complementary exam, such as a mammography. It is worth mentioning that this rare condition can affect males - less frequently - and affect other regions, such as the penis and scrotum. Furthermore, it is beneficial to recognize and diagnose Mondor syndrome, as surgeries using phytoaesthetics are constantly growing today, intending to guide patients in the best way possible for an effective and less invasive treatment (except in the concomitant presence of cancer). breast, for example), in addition to reassuring them about the condition.